PERAN GOOD CORPORATE GOVERNANCE DALAM MENINGKATKAN KUALITAS PELAYANAN DAN KEPUASAN NASABAH PADA BANK SYARIAH INDONESIA : STUDI KASUS : BSI CABANG MEDAN AKSARA - Aulia Syahfitri; Ahmad Wahyudi Zein; Miratul Imaniah; Nurhidayah; Maysa Chairani (CV. Barokah Publsiher, 2025)
This study aims to analyze the role of Good Corporate Governance in improving service quality and customer satisfaction at Bank Syariah Indonesia, Medan Aksara Branch. This study employs a qualitative approach using a case study method through in-depth interviews, direct observation, and analysis of internal bank documents. The implementation of Good Corporate Governance principles, which include transparency, accountability, responsibility, independence, and fairness, is systematically examined in relation to Islamic banking service practices. The findings indicate that the effective application of good corporate governance enhances employee professionalism, strengthens customer trust, and encourages consistency in service delivery in accordance with Islamic principles. High service quality has a direct impact on increasing customer satisfaction, as reflected in customer loyalty, positive perceptions, and comfort in conducting transactions. Furthermore, Good Corporate Governance functions as an internal control mechanism that helps prevent unethical practices and improves operational effectiveness. This study provides theoretical contributions to the development of Islamic banking governance studies and practical contributions for bank management in designing service strategies oriented toward customer satisfaction and institutional sustainability. The findings are expected to serve as a policy reference for improving Islamic banking services based on sustainable and competitive governance at both national and regional levels in the future of the financial industry.